The Influence of Work Discipline, Motivation, and Human Resource Development on Employee Performance - Putri Taopiq, Dyalda Tanesha; Fuziyati, Heti (Universitas KH. Abdul Chalim Mojokerto, 2024)
Human resources are the main driving element in all company activities, therefore, serious attention needs to be paid to the workforce. This research aims to evaluate the impact of work discipline, work motivation, and human resource development on employee performance at the Cirebon City Small, Medium Enterprises, Trade and Industry Cooperatives Service. The study population includes all employees in the Department, namely 56 people, all of whom were taken as samples. The data collection method uses a questionnaire. Data analysis was carried out through multiple linear regression, classical assumption test, multicollinearity test, heteroscedasticity test, multiple linear regression, T-test, F test, and coefficient of determination using SPSS version 29 for Windows software. The research results show that in partial testing, work discipline has a positive and significant effect on employee performance. The calculated value for the work discipline variable (X1) reached 4.834. This value exceeds the ttable value of 2.015, and significance (sig) has a value of 0.00 < 0.05. Thus, the hypothesis can be accepted, indicating that the work discipline variable (X1) has a significant influence on employee performance (Y). The t-count value of the human resource development variable (X3) is -0.772 < t table value, namely 2.015, and the sig value is 0.44 > 0.05, so the hypothesis is rejected. This means that the human resource development variable (X3) does not have a significant effect on employee performance (Y). The t-count value of the human resource development variable (X3) is -0.772 < t table value, namely 2.015, and the sig value is 0.44 > 0.05, so the hypothesis is rejected. This means that the human resource development variable (X3) does not have a significant effect on employee performance (Y). Based on the results of the calculated F value of 17.859 > F table value of 2.89 and the sig value of 0.000 < 0.05, H4 is accepted. This means that the variables of work discipline, and work motivation affect employee performance, while human resource development has no significant effect on employee performance in the Cirebon City Trade and Industry Cooperative, Small and Medium Enterprises department.